Association of race, ethnicity, and housing stability with COVID-19 testing method by investigators in underserved populations 2020–2023 - Woodhouse, Edwin Wilbur; Veldman, Timothy; Lydon, Elizabeth; Wruck, Lisa; Petzold, Elizabeth; Drain, Paul; Oren, Eyal; Kiene, Susan M.; McDaniels-Davidson, Corinne; Gwynn, Lisa; Perreira, Krista M.; Harper, Barrie; et al. (Frontiers in Public Health, 2025)
BackgroundExpanding SARS-CoV-2 testing was a critical part of community-based health efforts during the COVID-19 pandemic. In the RADx-UP consortium, a large NIH-funded network of community-engaged researchers in the United States, investigators were able to choose between PCR- and antigen-based testing strategies in community-based research settings. Data analyzing how COVID-19 diagnostics are chosen and utilized in research of vulnerable and underserved populations is limited.ObjectivesTo examine the association of race, ethnicity, and housing stability with a PCR- or antigen-based testing strategy within COVID-19 testing projects in the RADx-UP consortium.MethodsTesting protocols and investigator survey data describing target populations for community-engaged research projects were analyzed for association between race, ethnicity, and housing stability with SARS-CoV-2 test type. Community-engaged research projects were included if they were funded and approved to use PCR- and/or antigen-based COVID-19 testing by the RADx-UP testing core between 2020 and 2023. Multivariable adjustment to assess for confounding was then performed using rurality, project size, pandemic phase, and census region.ResultsSixty-seven projects (representing 479,410 participants) were included in the analysis. Overall, 24 (36%) projects chose an antigen-only testing strategy compared to 43 (64%) that chose a PCR-based strategy. No significant differences in distribution were seen in inclusion of PCR-testing by race (16 of 21 for Black race versus 27 of 46 for non-Black race, p = 0.198), ethnicity (22 of 33 for Hispanic ethnicity versus 21 of 34 for non-Hispanic ethnicity, p = 0.765), or housing stability (10 of 17 for unstable housing versus 33 of 50 for stable housing, p = 0.728) within intended population.ConclusionRace, ethnicity, and housing stability of an underlying vulnerable population was not significantly associated with the decision by community investigators regarding which COVID-19 testing strategy was most appropriate. Future research efforts should remain vigilant to offer emerging diagnostic technologies in the most equitable and appropriate ways.